Hubungan Kerja Kelompok Dengan Hasil Belajar Keterampilan Berbicara Mahasiswa Program Studi Pendidikan Bahasa Jerman - Melanius Sarbunan; Ida C Tamaela; Wilma Akihary (J-EDu: Journal - Erfolgreicher Deutschunterricht, 2021)
The purpose of this study was to describe the relationship between teamwork and learning outcomes of speaking skills. This type of research is descriptive quantitative using correlational analysis techniques and analyzed using product moment correlation. The research was conducted at the German Language Education Study Program, FKIP UNPATTI. The sample in this study were 30 Students of 4th semester. The data analysis technique used is a Likert Scale to measure the attitudes, opinions, and perceptions of respondents towards teamwork with a Likert scale. The results showed that the frequency of presentation of the results of the highest teamwork questionnaire score was 88 and the lowest score was 79. Then the results of speaking skills obtained the highest score of 100 and 18.75 for the lowest score. Furthermore, it is obtained that r is higher than rtable. Based on the results of the study, the hypothesis of this study can be accepted, namely ; there is a positive relationship between teamwork and learning outcomes of German speaking skills